STATE REGULATION OF STRUCTURAL REFORMS IN RAILWAY TRANSPORT OF UKRAINE - Kopytko, V. I. (Science and Transport Progress, 2008)
Some state regulation aspects of structural reforms on the railway transport ofUkrainetaking into account the transition to the organization new model (creation of the vertically integrated management structure that must conform to the modern criteria of economic activity) are considered in this article. It is proved that the structure of reformed railway branch must function due to internal reserves, be less dependent on external risks that will help to take efficient management decisions. Taking into consideration the transport effect on the world economy, it is necessary to adapt the railway branch structure to more efficient system of management capable of using the available resources, attracting the investments, which will promote to improve competitiveness of the railway transportation.